Brain abnormalities in children and adolescents with chronic kidney disease. (September 2018) - Matsuda-Abedini, Mina; Fitzpatrick, Kevin; Harrell, Waverly; Gipson, Debbie; Hooper, Stephen; Belger, Aysenil; Poskitt, Ken; Miller, Steven; Bjornson, Bruce
Abstract Background Chronic kidney disease (CKD) is a risk factor for vascular disease and stroke. The spectrum of brain injury and microstructural white matter abnormalities in children with CKD is largely unknown. Methods Cross sectional study at two North American pediatric hospitals. A cohort of 49 children, 29 with CKD, including renal transplant (mean age 14.4 ± 2.9 years; range 9–18), and 20 healthy controls (mean age 13.7 ± 3.1 years; range 9–18) had their conventional brain magnetic resonance images (MRIs) reviewed by one neuroradiologist to determine the prevalence of brain injury. Fractional anisotropy (FA) maps calculated from diffusion tensor imaging (DTI) were generated to compare white matter microstructure in CKD compared to controls, using tract-based spatial statistics (TBSS). Results Focal and multifocal white matter injury was seen on brain MRI in 6 children with CKD (21%). Relative to controls, CKD subjects showed reduced white matter fractional anisotropy and increased mean diffusivity and radial diffusivity in the anterior limb of the internal capsule, suggestive of abnormal myelination. Conclusion Cerebral white matter abnormalities, including white matter injury, are under-recognized in pediatric CKD patients. Brain imaging studies through progression of CKD are needed to determine the timing of white matter injury and any potentially modifiable risk factors.